Healing with basic fibroblast growth factor is associated with reduced indomethacin induced relapse in a human model of gastric ulceration. - Hull, M A (1997)
BACKGROUND: Acid stable basic fibroblast growth factor (bFGF) promotes angiogenesis and healing of gastric ulcers in rats and reduces subsequent non-steroidal anti-inflammatory drug (NSAID) induced relapse. AIMS: To test in a double blind, placebo controlled, three way crossover study whether bFGF promotes healing and reduces subsequent relapse in a human model of gastric ulceration. SUBJECTS: Twelve healthy volunteers. METHODS: Subjects took aspirin 900 mg twice daily (days 1-3) with bFGF 0.1 mg twice daily or cimetidine 400 mg twice daily or placebo (days 1-14) and then indomethacin 50 mg thrice daily (days 15-21). Endoscopy was performed on days 1, 4, 8, 15, and 22 during each treatment period. Eight antral biopsy specimens were taken on day 1 and the number of unhealed biopsy induced mini-ulcers and NSAID induced erosions counted during subsequent endoscopies. RESULTS: Basic FGF and cimetidine were protective against aspirin and indomethacin induced duodenal (but not gastric) injury compared with placebo. There was significant relapse of biopsy induced mini-ulcers after indomethacin only in the placebo group (0 (0-0) before v 1 (0-4.5) after; p > 0.05). TGP-580 was detected in serum of one volunteer. CONCLUSIONS: Healing with bFGF (and cimetidine) was associated with reduced NSAID induced ulcer relapse in this model of gastric ulceration.